Essentials of nuclear medicine imaging - Mettler, Fred A.; Guiberteau, Milton J. (Elsevier Saunders, 2012)
Essentials of Nuclear Medicine Imaging, by Drs. Fred A Mettler and Milton J Guiberteau, provides the practical and comprehensive guidance you need to master key nuclear imaging techniques. From physics, instrumentation, quality control, and legal requirements to hot topics such as sodium fluoride, radiopharmaceuticals, and recommended pediatric administered doses and guidelines, this sixth edition covers the fundamentals and recent developments in the practice of nuclear medicine. Get comprehensive coverage of key techniques such as PET/CT, cardiac-gated SPECT, and tumor-specific radionuclides, as well as Cerebrovascular System, Cardiovascular System, Conventional Neoplasm Imaging and Radioimmunotherapy, and Positron Emission Tomography Imaging. Reference practical clinical guidance at a glance from important "Pearls and Pitfalls" in each chapter and. helpful appendices including Injection Techniques, Pediatric Dosages, Non-radioactive Pharmaceuticals, and many more Assess your understanding with a section of Unknown Case Sets-expanded in this edition. Find information quickly and easily with a full-color format. Apply the latest best practices thanks to extensive updates of clinical guidelines that reflect recent changes in the practice of nuclear medicine, including the use of sodium fluoride (F-18 FDG for infections and Na F-18 for skeletal imaging), suggested radiopharmaceuticals for imaging various types of tumors, and imaging procedures and new classification schemes for pulmonary embolism. Effectively use PET/CT in imaging neoplasms with coverage of the most current indications. Manage radition safety concerns using quality control procedures for hybrid imaging equipment, patient and radiation safety checklists for I-131 therapy for hyperthyroidism and thyroid cancer, and recommended pediatric administered doses and guidelines. Get a clear view of the current state of imaging from high-quality images - 35% new to this edition.